Avaliação da influência do hidrogênio na tenacidade quase estática de uma junta soldada dissimilar constituída com o aço AISI 8630M amanteigado com ER80S-D2 - Cavalcante, Fabrício José Nóbrega (2014)
The steady growth in the use of structural steel has been studied by researchers and companies in underwater applications with the use of solder joints with dissimilar steels. To apply this type of joint in this type of environment, makes use of cathodic protection systems, which promotes the release of hydrogen ions favoring the appearance of unexpected fractures in materials. In the study, were fabricated joints of AISI 8630M previously buttered with the electrode AWS ER80S-D2 (on low carbon steel) for evaluation. Hardness and microhardness tests with and without heat treatment for stress relief, tensile test of the base metal and weld metal, and determining fratrura toughness of the base metal and weld were performed with and without the presence hydrogen, determining and comparing the fracture toughness through the CTOD parameter. The results showed that the buttery stuff in decreased hardness and hardness when it was heattreated, with greater intensity in the heat affected zone region besides having a better uniformity in the results. For the final welding, the welding power is used in the union of dissimilar joint, did not alter the properties of the buttery stuff. CTOD The results indicated a reduction in toughness of the base metal fracture by 25% and 11% in the welded joint. And fractográficas analyzes showed that, despite the influence of hydrogen, the micromechanics of fracture, showed up for ductile general